THE ROLE OF THE AGILE LEADERSHIP MODEL AS A COMPETITIVE ADVANTAGE FOR THE FUTURE LEADER IN THE ERA OF GLOBALIZATION AND INDUSTRIAL REVOLUTION 4.0 - Angga Prasongko; Tri Adianto (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2019)
The world development has entered the Globalization and Industrial Revolution 4.0 era. People are required to have new literacy skills for facing some changes in their life. The new literacy skills are data literacy, technological literacy, and human literacy, as a basic capital for taking part in social life. One of the abilities that need to be owned and has an important role in an individual's competitive advantage is the ability to lead the society. One way to develop this capability is through the application of agile leadership models. This leadership model can create a figure of leader who is calm, adaptable, innovative, always learning from experience and give feedback, helpful, smart to see opportunities, adaptive, agile, open-minded and have a high ambiguity acceptance while still maintaining the productivity and achievement of the company's main goals at the same time. The agile leadership model should be considered to be applied in the Industrial Revolution 4.0 era because the fast-changing world requires a figure of leader who is calm, adaptable, innovative, always learning from experience and give feedback and motivate to help others and think for next generation.Keywords: Agile Leadership, Competitive Advantage, Globalization, Industrial Revolution 4.0 era